Pengaruh Coping Stres Dan Harga Diri Terhadap Kesehatan Mental Remaja di yayasan Darusallam Kota Bengkulu - Oktamah Putri, Kurnia; Desiska, Anggelya; Febrianto, Reza; Badriyah, Lailatul (DAWUH : Islamic Communication Journal, 2022)
This research aims to examine the influence of stress coping and self-esteem on the mental health of adolescents at the Darusalam Foundation in Bengkulu City. This research uses quantitative methods, the data collection technique is by distributing a questionnaire of 30 items. The samples studied were teenagers at the Darusalam Foundation, Bengkulu City. Data were collected from 107 respondents. This research was analyzed using quantitative analysis using SPSS by testing correlation regression, normality test, reliability test and R Square. Based on the results of this study, it shows the influence of stress coping and self-esteem on the mental health of teenagers at the Darusallam Foundation, Bengkulu City. is in the weak category, namely 28.3%.